2013
DOI: 10.1371/journal.pone.0073269
|View full text |Cite
|
Sign up to set email alerts
|

Averting HIV Infections in New York City: A Modeling Approach Estimating the Future Impact of Additional Behavioral and Biomedical HIV Prevention Strategies

Abstract: BackgroundNew York City (NYC) remains an epicenter of the HIV epidemic in the United States. Given the variety of evidence-based HIV prevention strategies available and the significant resources required to implement each of them, comparative studies are needed to identify how to maximize the number of HIV cases prevented most economically.MethodsA new model of HIV disease transmission was developed integrating information from a previously validated micro-simulation HIV disease progression model. Specificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…We have shown that 24% of new HIV infections could be averted with modest assumptions about PrEP uptake and effectiveness when utilized within the larger community at-risk of HIV acquisition in NYC. We have previously reported on less expensive combination prevention strategies that are able to avert similar proportions of HIV infections over a similar time frame [17]. Prioritizing PrEP to high-risk populations would be reasonable to produce health gains in an economically feasible and efficient manner [30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown that 24% of new HIV infections could be averted with modest assumptions about PrEP uptake and effectiveness when utilized within the larger community at-risk of HIV acquisition in NYC. We have previously reported on less expensive combination prevention strategies that are able to avert similar proportions of HIV infections over a similar time frame [17]. Prioritizing PrEP to high-risk populations would be reasonable to produce health gains in an economically feasible and efficient manner [30].…”
Section: Discussionmentioning
confidence: 99%
“…This mathematical model integrates equilibrium results from a Monte Carlo simulation of HIV progression with a deterministic compartmental model of HIV transmission [17]. The model incorporates both sexual transmission and transmission through needle-sharing during injection drug use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research by Vickerman and colleagues [46] indicates that the hepatitis C coinfection prevalence among HIV positive PWID may be an important marker for understanding the proportion of HIV infections due to injection versus sexual transmission among PWID. Bioly and Shubber note that recent models indicate that PrEP and treatment-as-prevention may be cost-effective but ideally targeted towards higher risk individuals [4749], and that needle and syringe exchange programs, opioid-substitution therapy, and condom use are highly cost-effective [5054] and, in some settings, may be sufficient to substantially reduce long-term HIV prevalence [55;56]. …”
Section: Methodological Challenges and Advancesmentioning
confidence: 99%